2021
DOI: 10.30748/soi.2021.166.03
|View full text |Cite
|
Sign up to set email alerts
|

Development of a protocol for a closed mobile internet channel based on post-quantum algorithms

Abstract: The development of computing technologies has made it possible not only to expand the range of mobile communication services, but also to significantly increase computing capabilities. The emergence of mobile Internet, 4G, 5G technologies makes it possible to talk about a fundamentally different approach to ensuring the quality of service to network customers, creating fundamentally new approaches to ensuring the efficiency and reliability of transmitted information flows. However, such a rapid growth of GSM t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Althoug scheme provides minimum error, it has limitations in scalability, key managemen consensus overhead. In [164], the authors proposed McEliece and Niederreiter c code on elliptic codes for quantum-resistant authentication in a closed mobile in Similarly, the authors in [163] suggested a blockchain-based authentication for heterogenous devices to provide joint authentication and access control. Although this scheme provides minimum error, it has limitations in scalability, key management and consensus overhead.…”
Section: Multi-factor Authenticationmentioning
confidence: 99%
See 1 more Smart Citation
“…Althoug scheme provides minimum error, it has limitations in scalability, key managemen consensus overhead. In [164], the authors proposed McEliece and Niederreiter c code on elliptic codes for quantum-resistant authentication in a closed mobile in Similarly, the authors in [163] suggested a blockchain-based authentication for heterogenous devices to provide joint authentication and access control. Although this scheme provides minimum error, it has limitations in scalability, key management and consensus overhead.…”
Section: Multi-factor Authenticationmentioning
confidence: 99%
“…Although this scheme provides minimum error, it has limitations in scalability, key management and consensus overhead. In [164], the authors proposed McEliece and Niederreiter crypto-code on elliptic codes for quantum-resistant authentication in a closed mobile internet channel. The scheme provides an offline mode for closing the voice channel; however, the employed algorithms are sensitive to fault injection attacks.…”
Section: Multi-factor Authenticationmentioning
confidence: 99%